2019
DOI: 10.31665/jfb.2019.5175
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins and intestinal barrier function: a review

Abstract: Chronic intestinal inflammation, occurring in inflammatory bowel diseases (IBD), is associated with compromised intestinal barrier function. Inflammatory cytokines disrupt tight junctions and increase paracellular permeability of luminal antigens. Thus, chronic intestinal barrier dysfunction hinders the resolution of inflammation. Dietary approaches may help mitigate intestinal barrier dysfunction and chronic inflammation. A growing body of work in rodent models of colitis has demonstrated that berry consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 128 publications
0
18
0
Order By: Relevance
“…Thus, fruits having ferulic acid with epigallocatechins appeared to be more effective inhibiting IC-induced barrier dysfunction in Caco-2 cells. Prior studies have also demonstrated the ability of FA to inhibit inflammation and protect gastrointestinal cells and TJ [24][25][26]. FA in Gulupa, Maracuyá, and Granadilla extracts showed TEER improvement (Table 3) of Caco-2 cells.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, fruits having ferulic acid with epigallocatechins appeared to be more effective inhibiting IC-induced barrier dysfunction in Caco-2 cells. Prior studies have also demonstrated the ability of FA to inhibit inflammation and protect gastrointestinal cells and TJ [24][25][26]. FA in Gulupa, Maracuyá, and Granadilla extracts showed TEER improvement (Table 3) of Caco-2 cells.…”
Section: Discussionmentioning
confidence: 79%
“…Caco-2 cells were treated with an inflammatory cocktail (IC) consisting of inflammatory cytokines IL-1β (25 ng/mL), TNF-α (50 ng/mL), IFN-γ (50 ng/mL), and pro-inflammatory lipopolysaccharide (LPS) (1 mg/mL) for 48 h. The IC was formulated to model intestinal barrier dysfunction induced by chronic inflammation as described previously [24]. Growth media, as a control, of the IC (880 µL) were pipetted into the basolateral compartment of Transwell plates.…”
mentioning
confidence: 99%
“…The protective effect of consumption of phenolic-rich grains, legumes, berries, nuts, and oilseeds against several chronic diseases was demonstrated by several researcher groups (Valdez et al, 2019;Shahidi et al, 2019aShahidi et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…Blue flowers such as cornflower, blue chicory and blue rosemary and purple flowers such as purple mint, purple passionflower, purple sage, common violet and lavender are the common edible flowers. Some of the fruits containing anthocyanins include cherries, plums, strawberries, raspberries, blackberries, grapes, red currants and black currants (Shahidi and Ambigaipalan, 2015;Valdez and Bolling, 2019). Stability of anthocyanins is dependent on the type of anthocyanin pigment, copigments, metal ions, light, pH, temperature, oxygen, enzymes and antioxidants (Castañeda-Ovando et al, 2009;Khoo et al, 2017;Pietta et al, 2003).…”
Section: Anthocyanidins and Anthocyaninsmentioning
confidence: 99%